(untitled) (Journal of the College of Basic Education, 2022)
The aim of this work is to use Bernstein polynomials for deriving some modified quadrature methods for solving systems of the onedimensional Volterra linear integral equations of the second kind. These are modified Trapezoidal rule and the modified Simpsons 3/8 rule of the first order.For each method, some numerical examples are solved and computer are written in (Excel), And the results are presented in tabulated forms.